(untitled) (Research, Society and Development, 2021)
Objective: to analyze the knowledge built in theses and dissertations of the Brazilian Graduation Degree about the technologies for systemic arterial hypertension. Method: documentary research, carried out in July 2020, in the Thesis and Dissertation Catalog of the Coordination for the Improvement of Higher Education Personnel, through two search strategies: technology AND hypertens* and technology AND “blood pressure”. After applying the selection criteria, 21 productions composed the final corpus for analysis. Results: most of the productions were dissertations, produced in the Northeast region, by the nursing area, in 2018 and with the methodological research method. Educational technologies were predominant, with the purpose of health education, focused on the prevention and control of systemic arterial hypertension. Moreover, technologies for teaching and improving blood pressure measurement, providing continuing health education and managing the care of users with systemic arterial hypertension were also developed. Final Considerations: health technologies contribute to the care provided to users with systemic arterial hypertension. Technologies for health education are trends of the production of knowledge, constituting themselves as powerful strategies. It is inferred that the development of technologies for continuing health education and for care management is also important.